Answer:
x = 4 or x = -2 or x = 3 i or x = -3 i
Explanation:
Solve for x:
3 (x^4 - 2 x^3 + x^2 - 18 x - 72) = 0
Divide both sides by 3:
x^4 - 2 x^3 + x^2 - 18 x - 72 = 0
The left-hand side factors into a product with three terms:
(x - 4) (x + 2) (x^2 + 9) = 0
Split into three equations:
x - 4 = 0 or x + 2 = 0 or x^2 + 9 = 0
Add 4 to both sides:
x = 4 or x + 2 = 0 or x^2 + 9 = 0
Subtract 2 from both sides:
x = 4 or x = -2 or x^2 + 9 = 0
Subtract 9 from both sides:
x = 4 or x = -2 or x^2 = -9
Take the square root of both sides:
Answer: x = 4 or x = -2 or x = 3 i or x = -3 i
PS: next time, please present the equation properly and do not make us guess.